Adults and Higher Education: Bridging the Culture Gap - Maurice Olivier (Educational Considerations, 1986)
Serving rural adult learners requires a basic and fundamental understanding of both the culture of adulthood and the culture of higher education. This paper explores a model for bridging the two cultures.